DESKRIPSI SOSIAL BUDAYA MASYARAKAT DESA HUTAN GUNUNG MEKONGGA - Nur Arafah; Alamsyah Flamin; Arniawati Arniawati; Muhafidz Muhafidz (Jurnal Ecogreen, 2015)
This study aims to determine the social cultural condition of Tinukai village in Mekongga Mountain Forest preservation that was condition in Tinukari village Wawo sub-district, North Kolaka which lasted for 2 months, May to June by sowball sampling technique. The result of that stydy shows that Tinukari village is inhabited by indigous people of Tolaki Mekongga since the 1980s, and by 1990s in Tinukari was began inhabited by several migrants ethnic south Sulawesi such the Bugis (Luwu and Sinjai) Makassar, Toraja and Kajang, and 1997 the Tinukari Village was definitifly estabilished. The Tinukari Villagers belief system is based on islamic belief. In the social and cultural interaction, the formal social stratifition only recognize head of the village (kepala desa) religious figures, and costume leaders. The social of society appears in the from of cooperation, competition, conflict and accomodation. Patterns leadership in social structure Tinukari consist of administrative leadership, traditional leadership, and religious leadership. Institutions an sanction (law) hat exist in the community in the form of goverment institutions, religious institutions and customary structures. Natural resources governance that recognized by the community include the state forest to open and clear he land for plantations and agriculture initiated by their parents as normadic society (normad). There are no writen rules in utilization of land resources but depends only on awareness of social norms and respect the nature values. Those who violate the norms could be given a reprimand the nature communities members and local goverment. Keywords: Social Culture, Society, Forest, Gunung Mekongga